How Can Science and Research Work Well? Toward a Critique of New Public Management Practices in Academia From a Socio-Philosophical Perspective - Kruse, Jan-Philipp (Frontiers in Research Metrics and Analytics, 2022)
While New Public Management practices (NPM) have been adopted in academia and higher education over the past two decades, this paper is investigating their role in a specifically socio-philosophical way: The preeminent question is what organization of science is likely to make science and research work well in the context of a complex society. The starting point is an obvious intuition: that academia would be ‘economized’ by NPM (basically, that something is coming from the outside and is disturbing the inside). Habermas provides a sophisticated theorization for this intuition. In contrast, the thesis advanced here is that we should consider NPM potentially problematic – but not for descending from economics or administration outside academia. It is because NPM often cannot help research and science to function well. In this (rather ‘essayistic’ than strictly deductive) consideration, I will therefore tentatively discuss an alternative approach that takes up critical intuitions while transposing them into a different setting. If we understand science and research as a form of life, a different picture emerges that can still bring immanent standards to bear, but at the same time compose them more broadly. This outlines a socio-philosophical critique of NPM. Accordingly, the decisive factor is not NPM’s provenance. What is decisive is that it addresses some organizational problems while at the same time creating new ones. At the end, an outlook is sketched on how the specific situation of NPM allows some hypotheses on academy’s future organization. Ex negativo, it seems likely that qualitative evaluation criteria and creative freedom will have to play a greater role.